2017
DOI: 10.21595/vp.2017.19442
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and damping characteristics of adaptive materials for layered structures

Abstract: Compositions of high-filled magnetically controlled materials with different dispersed phase particle sizes are developed. Rheological and damping characteristics of materials in the system of oscillations of three-layer plates are determined and their dependence on the size of magnetically sensitive particles is established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…For rheological experiments, a Physica MCR 301 of Anton Paar rheometer was used (plate-plate measuring cell, plate diameter is 20 mm, the gap is 0.7 mm) with a change in the magnetic field induction B up to 1 T. We have previously (Zhurauski et al, 2017) measured such rheological characteristics of these MCM compositions as flow curves, static yield stress, complex shear modulus, as well as their damping characteristics in an oscillation system of three-layer flat structural elements. It was shown that with a decrease in the size of carbonyl iron particles, the shear stress under continuous flow and the yield stress value increase (by more than two times at B = 1 T).…”
Section: Materials and Equipmentmentioning
confidence: 99%
“…For rheological experiments, a Physica MCR 301 of Anton Paar rheometer was used (plate-plate measuring cell, plate diameter is 20 mm, the gap is 0.7 mm) with a change in the magnetic field induction B up to 1 T. We have previously (Zhurauski et al, 2017) measured such rheological characteristics of these MCM compositions as flow curves, static yield stress, complex shear modulus, as well as their damping characteristics in an oscillation system of three-layer flat structural elements. It was shown that with a decrease in the size of carbonyl iron particles, the shear stress under continuous flow and the yield stress value increase (by more than two times at B = 1 T).…”
Section: Materials and Equipmentmentioning
confidence: 99%